Essay on Virtues (1949) and Somewhere in the Unfinished (1978) - Prelorentzos, Ioannis (Conatus - Journal of Philosophy, 2018)
Greek translation of Vladimir Jankélévitch, Traité des vertus (Paris: Bordas, 1949), and Béatrice Berlowitz and Vladimir Jankélévitch, Quelque part dans l’inachevé (Paris: Gallimard, 1978).